Synthesis of iron-based high temperature superconductors - Tan, Bryan Wen Wei. (2009)
In February 2008, a new superconductor family was discovered. This project aims to discuss the various methods used to synthesize these compounds and the different crystal growth methods used. First papers reported that these new superconducting materials have been synthesized within a closed system, which poses the risk of an explosion due to the high arsenic vapor pressure. The purpose of this experiment is to devise a method and to investigate the viability of synthesizing iron-based high-temperature superconductors, namely LaFeAsO1-xFx in an open system. In addition, the use of an antimony flux to grow single crystals of LaFeAsO1-xFx will be investigated. This project shows the successful design of an open system to synthesize materials of LaFeAsO1-xFx. Antimony was also found to be a usable flux in growing the superconducting materials. Furthermore, various methods of synthesizing single crystals of FeAs, such as the Bridgeman method and iodine vapor transport, for the usage of future tests were explored and were also found to be successful.